Egyptian Scarabs in Southwest Canaan in the Late Bronze and Iron I: Observations from a Local Perspective - Koch, Ido (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Throughout the second and first millennia BCE, one of the hallmarks of Levantine-Egyptian interaction was consumption in the Levant of Egyptian-style amulets, with special preference given to imported Egyptian scarabs. The early phases of this consumption were further intensified during the Middle Bronze II, following the emergence of prosperous Levantine production, appropriating Egyptian concepts and developing a rich local pictorial sphere (Ben-Tor 2007). In the Late Bronze I and more visibly in the Late Bronze IIA, in what was a gradual and protracted process, Egyptian imports largely replaced the locally produced scarabs, reaching the zenith of their popularity during the Late Bronze IIB (Lalkin 2008). Both imported and locally produced scarabs have been found, mainly in burials, sometimes combined with additional items, reflecting their function as charms (Keel 1995).